A 3-Year Chronic Disease Public Health Intervention Focused on a Network of Rural Pharmacies Supported by Student Pharmacists. (August 2021) - Nuffer, Wesley; Gilliam, Eric; Trujillo, Tara; Griend, Joseph Vande; Thompson, Megan
Objective: To retrospectively analyze and report various tracked outcomes of a 3-year collaboration offering chronic disease management services in diabetes and cardiovascular disease in pharmacies across 12 rural communities supported year-round by fourth-year student pharmacists. Methods: Individualized medication therapy management services were provided to patients with cardiovascular disease and diabetes in a 6-month series based upon national guidelines standards of care. Objective laboratory measurements, adherence rates, goals set for patients, vaccination rates, and routine maintenance examinations were all tracked as part of the program. Provider acceptance of recommendations from student pharmacists were tracked, and patients completed a 3-question survey regarding satisfaction with services. Results: A total of 430 student pharmacists rotated through these pharmacy sites providing care to 779 unique patients across 3 years. Statistically significant improvements in A1C (−0.8%, P < .001) and systolic and diastolic blood pressure (5 mm Hg, 3 mm Hg, respectively, P < .01) were associated with the pharmacy care. Adherence issues were identified and addressed with 44% of these patients. In all, 70% of patients reported successful goal attainment of >50% from baseline. Providers accepted student therapy change recommendations 56% of the time. Patients reported satisfaction with services provided in the pharmacies (average scores of 4.22-4.67 on a 1-5 Likert-type scale). Conclusions: A 3-year pharmacy intervention in 12 rural areas made positive impacts on patients' adherence rates and self-management in diabetes and cardiovascular disease and was associated with statistically significant improvements in A1C and blood pressure while challenging fourth-year student pharmacists to perform at a high level on community pharmacy rotations.